(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The objective was to evaluate diluents and transport systems on semen quality frozen by CASA in Nellore bulls. Five semen collections of six bulls, diluted with the TRIS and BotuBOV®, were transported out on two types of BotuBOX® and BotuFLEX® systems; frozen and analyzed by CASA. TM was higher (p <0.05) in the association of BotuBOV® + BotuFLEX® (47.3%) when compared to TRIS + BotuBOX® (9%). The PM was higher (p <0.05) BotuBOV® + BotuFLEX® (37%) when compared to TRIS + BotuBOX® (5.9%). The same for VSL, BCF and RAP, which were higher (p <0.05) in BotuBOV® + BotuFLEX® (65.1μm/s, 30Hz, 44.5%, respectively) when compared to semen in the TRIS + BotuBOX® (47.6μm/s, 21.5Hz, 6.9%, respectively). It is concluded that BotuBOV® in association with the refrigerated system of semen BotuFLEX® was considered by CASA to be the best association when referring to sperm kinetics for cryopreservation of bovine semen.